Factors Contributing to Catch-Up Growth of Child with Stunting: A Literature Review - Ayuni Rizka Utami; Nani Nurhaeni (STRADA : Jurnal Ilmiah Kesehatan, 2021)
Stunting is the main problems for children in Indonesia, children who are already stunted can catch-up growth to minimize the impact of stunting. This literature study aims to identified the factors contribute to catch-up growth in children with stunting. Literature search several online databases with the keyword "Factors AND Stunting Catch-up Growth AND Child *". The selected articles were articles published in 2016-2020 in English and used a sample of children with stunting. The results of the literature study found 555 articles and 9 articles that met the inclusion and exclusion criteria. Several major factors that contribute to the catch-up growth of children with stunting are the level of education and height of the mother, economic status, socio-culture, nutritional supplements and community based intervention. Contributing factors can be used as considerations in providing interventions to support catch-up growth in children with stunting so as to reduce the impact of stunting.